Study comparing phenylephrine bolus and infusion for management of perioperative hypotension in elective LSCS under spinal anaesthesia - Gyawali, Madhu; Devi Sharma Regmi, Bharati; Prasad Singh, Jaya; Prasad Deo, Gopendra; Krishna Yadav, Nabin; Ghimire, Ramesh; Kumar Gyawali, Parbesh; Bastola , Ramjee (Journal of Chitwan Medical College, 2025)
Introduction: Phenylephrine bolus and infusion were compared for effectiveness in treating post-spinal hypotension, and observing neonatal outcomes. Method: This was a prospective, randomized, comparative study conducted in the department of Anaesthesia at Chitwan Medical College, Nepal, from 23 Feb 2022 to 22 Feb 2023 after ethical approval from CMC-IRC. Under inclusion criteria, 84 parturients were randomized into 2 groups with 42 patents in each. Group A received 50 µg bolus phenylephrine after systolic blood pressure fell by 20%, Group B received a prophylactic infusion of 50 µg/min of phenylephrine. Changes in blood pressure and heart rate were noted. Neonatal APGAR score and side effects were compared. Statistical analysis was done with SPSS version 23 using a T-test and frequency table, p<0.05 was considered significant. Result: Systolic blood pressure was significantly greater over time in Group B as compared to Group A. Incidence of maternal hypotension in Group A was 35(83.3%) and 10(23.8%) in Group B. Similarly, the incidence of nausea was high i.e. 10(23.8%) in Group A compared to 1(2.4%) in Group B. At the same time, the incidence of vomiting was higher in Group A as compared to Group B. The APGAR Scores of both groups were similar. Injection of Mephentermine as a rescue drug was needed more times in Group A than in Group B. Injection of Atropine was needed more frequently in Group B. Conclusion: Phenylephrine infusion is superior to phenylephrine bolus for control of haemodynamics with lesser side effects in elective caesarean under spinal anaesthesia.